Introgressing Subgenome Components from Brassica rapa and B. carinata to B. juncea for Broadening Its Genetic Base and Exploring Intersubgenomic Heterosis - Wei, Zili; Wang, Meng; Chang, Shihao; Wu, Chao; Liu, Peifa; Meng, Jinling; Zou, Jun (Frontiers in Plant Science, 2016)
Brassica juncea (AjAjBjBj), is an allotetraploid that arose from two diploid species, B. rapa (ArAr) and B. nigra (BnBn). It is an old oilseed crop with unique favorable traits, but the genetic improvement on this species is limited. We developed an approach to broaden its genetic base within several generations by intensive selection. The Ar subgenome from the Asian oil crop B. rapa (ArAr) and the Bc subgenome from the African oil crop B. carinata (BcBcCcCc) were combined in a synthesized allohexaploid (ArArBcBcCcCc), which was crossed with traditional B. juncea to generate pentaploid F1 hybrids (ArAjBcBjCc), with subsequent self-pollination to obtain newly synthesized B. juncea (Ar/jAr/jBc/jBc/j). After intensive cytological screening and phenotypic selection of fertility and agronomic traits, a population of new-type B. juncea was obtained and was found to be genetically stable at the F6 generation. The new-type B. juncea possesses good fertility and rich genetic diversity and is distinctly divergent but not isolated from traditional B. juncea, as revealed by population genetic analysis with molecular markers. More than half of its genome was modified, showing exotic introgression and novel variation. In addition to the improvement in some traits of the new-type B. juncea lines, a considerable potential for heterosis was observed in inter-subgenomic hybrids between new-type B. juncea lines and traditional B. juncea accessions. The new-type B. juncea exhibited a stable chromosome number and a novel genome composition through multiple generations, providing insight into how to significantly broaden the genetic base of crops with subgenome introgression from their related species and the potential of exploring inter-subgenomic heterosis for hybrid breeding.